Semitransparent laminated perovskite cell

By adopting stacked structure and laser etching technology in translucent perovskite batteries, the problems of material stability and photoelectric performance balance are solved, and high-efficiency energy conversion and appropriate transparency are achieved, which promotes translucent perovskite batteries in Applications in the field of integrated photovoltaics in the building.

CN119403345APending Publication Date: 2025-02-07FLAT GLASS GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411469477.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing translucent perovskite batteries have challenges in achieving a balance between efficient energy conversion and transparency, especially in terms of material stability, long-term use performance, and large-scale production technology.

Method used

A translucent laminated perovskite battery structure is adopted, including a glass substrate, NiOx layer, perovskite layer, PCBM layer, AgNW electrode layer and C60 electrode layer. The perovskite layer is micro-patterned by laser etching technology. Optimize material composition and structural design to improve the balance of electrical and optical properties.

Benefits of technology

Achieving PCE with up to 9.0% at 44% AVT conditions while maintaining neutral color presentation and low haze of industrial glass quality, demonstrating the ability to expand from individual solar cells to submodules and by introducing transmission gradients Design enhances the diversity of architectural aesthetics and functions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005094306320000011
    Figure HDA0005094306320000011
Patent Text Reader

Abstract

The invention relates to a semitransparent laminated perovskite cell, and belongs to the technical field of perovskite cells, the perovskite cell comprises a glass substrate, a NiOx layer, a perovskite layer, a PCBM layer, an AgNW electrode layer and a C60 electrode layer, the glass substrate, the NiOx layer, the perovskite layer, the PCBM layer, the AgNW electrode layer and the C60 electrode layer are sequentially arranged from bottom to top, and the perovskite layer is subjected to micro-patterning treatment through a laser etching technology. The prepared perovskite solar cell has a PCE of up to 9.0% under 44% AVT, and at the same time maintains neutral color presentation and low haze of industrial glass quality; the expansion capability from a single solar cell to a sub-module is demonstrated, and the sub-module realizes 9.0% PCE at 32% AVT under the aperture area of 4 cm < 2 >; the expandability of the technology ensures that the transparent perovskite photovoltaic technology is applied to actual buildings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite cells, and in particular to a semi-transparent laminated perovskite cell. Background Art

[0002] As a representative of the new generation of photovoltaic technology, semi-transparent perovskite cells have received extensive attention in recent years due to their unique optoelectronic properties and potential for wide application prospects. Perovskite materials have excellent light absorption ability, long carrier diffusion length, high charge mobility and other advantages, making perovskite solar cells outstanding in energy conversion efficiency and gradually becoming a hot spot in photovoltaic research. In the development of semi-transparent perovskite cells, achieving a balance between efficient energy conversion and transparency is one of the key technologies.

[0003] Although traditional silicon-based cells are highly efficient, their opacity limits their use in building-integrated photovoltaics (BIPV) and other applications with high aesthetic requirements. In contrast, semi-transparent perovskite cells can integrate photovoltaic technology into transparent scenes such as building glass and vehicle windows, while maintaining a certain light transmittance, providing more possibilities for architectural design. In terms of specific technical implementation, the core of semi-transparent perovskite cells lies in material selection and structural design. First, the composition and thickness of perovskite materials need to be optimized so that they can exhibit excellent light absorption and appropriate light transmittance within a specific wavelength range. Secondly, the electrode materials and transparent conductive layers of the battery are also key elements, ensuring that they minimize the blocking of visible light while maintaining high conductivity. In addition, multi-layer structural design and light management technology, such as the introduction of a back reflective layer, can also help improve the overall photoelectric performance of the battery. At present, research on semi-transparent perovskite cells has made some progress, but it still faces some challenges, such as material stability, long-term performance, and large-scale production technology. The solution to these problems will promote the wider commercial application of semi-transparent perovskite cells and may become one of the important development directions of photovoltaic technology in the future. Summary of the invention

[0004] In order to overcome the above-mentioned defects of the prior art, the present invention provides a semi-transparent laminated perovskite cell that can balance electrical and optical properties and can be used in actual buildings.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides a semi-transparent laminated perovskite cell, wherein the perovskite cell comprises a glass substrate, a NiOx layer, a perovskite layer, a PCBM layer, an AgNW electrode layer, and a C60 electrode layer, wherein the glass substrate, the NiOx layer, the perovskite layer, the PCBM layer, the AgNW electrode layer, and the C60 electrode layer are sequentially arranged from bottom to top, and the perovskite layer is micro-patterned by laser etching technology.

[0006] Furthermore, the method for preparing the NiOx layer includes:

[0007] The glass substrate was first cleaned in ultrasonic waves with detergent, deionized water, acetone, and IPA in sequence, and then dried and treated with UV ozone at 100 degrees Celsius for 10 minutes;

[0008] Spin coating the NiOx ink on the glass substrate at 3000 rpm for 45 seconds, followed by drying on a hot plate at 100 degrees Celsius for 10 minutes to prepare a NiOx layer;

[0009] The preparation method of the NiOx ink comprises:

[0010] 3.635 g of nickel nitrate was dissolved in 2.5 ml of water, and about 2.5 ml of 10 M sodium hydroxide solution was slowly added to the solution to generate a light green Ni(OH)2 precipitate. The precipitate was collected by centrifugation and washed three times with deionized water. The precipitate was transferred to an 80°C oven and dried until the color turned dark green. The solid was then transferred to a 270°C oven and calcined for 2 hours to obtain NiOx nanoparticles. Finally, the NiOx nanoparticles were dispersed in deionized water at a concentration of 2.6 wt%, and ultrasonically treated for 2 hours and then filtered.

[0011] Furthermore, the method for preparing the perovskite layer includes:

[0012] In a glove box, the perovskite precursor solution was spin-coated on the NiOx layer using an anti-solvent technique at speeds of 2000 rpm and 6000 rpm for 10 seconds and 30 seconds, respectively. When the second stage of spin coating was about 10 seconds, 100 μl of chlorobenzene was added. After the spin coating was completed, the substrate was immediately transferred to a 100°C hot plate and kept warm for 50 minutes.

[0013] Furthermore, the preparation method of the PCBM layer includes:

[0014] First, a PCBM solution was prepared by dissolving PCBM in DCB at a concentration of 23 mg / ml, and then filtering to form a PCBM solution. The PCBM solution was then spin-coated at 1300 rpm for 40 seconds to form an ETL layer, followed by annealing at 100 degrees Celsius for 5 minutes and cooling for later use.

[0015] Furthermore, the preparation method of the AgNW electrode layer includes:

[0016] On the PCBM layer, AgNW dispersion was spin-coated at a speed of 900 rpm for 30 seconds and then dried at 90 degrees Celsius for 30 seconds. Polyimide tape was used as a mask to define the pattern area of ​​the AgNW electrode. The active cell area was typically 0.09 cm 2, the electrode thickness was increased by repeating the spin coating process.

[0017] Furthermore, the preparation method of the C60 electrode layer includes:

[0018] First, prepare a C60 solution, dissolve 10 mg / ml of C60 in DCB, heat to 60° C. to dissolve, and then spin-coat the 10 mg / ml C60 solution on the AgNW electrode layer at a spin-coating speed of 1300 rpm for 45 seconds.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. Balance between electrical and optical properties:

[0021] The prepared perovskite solar cells have a PCE of up to 9.0% at 44% AVT while maintaining industrial glass-quality neutral color rendering and low haze;

[0022] 2. Scalability:

[0023] Demonstrated scalability from single solar cells to submodules, achieving 9.0% PCE at 32% AVT with an aperture area of ​​4 cm2;

[0024] The scalability of the technology ensures that these transparent perovskite photovoltaic technologies can be applied in real buildings;

[0025] 3. Prospects of building integrated photovoltaics:

[0026] By introducing the transmission gradient design, the diversity of architectural aesthetics and functions is improved. This design not only meets the needs of photovoltaic energy collection, but also increases the aesthetics and personalization possibilities of the building facade. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic cross-sectional structural diagram of an embodiment of the present invention. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the invention, rather than all the embodiments. The embodiments of the present invention are described below in conjunction with the drawings.

[0029] refer to Figure 1A semi-transparent laminated perovskite cell comprises a glass substrate 1, a NiOx layer 2, a perovskite layer 3, a PCBM layer 4, an AgNW electrode layer 5, and a C60 electrode layer 6, wherein the glass substrate 1, the NiOx layer 2, the perovskite layer 3, the PCBM layer 4, the AgNW electrode layer 5, and the C60 electrode layer 6 are sequentially arranged from bottom to top, and the perovskite layer 3 is micro-patterned by laser etching technology;

[0030] By performing micro-patterning on the perovskite layer 3, transparent areas are produced in specific areas. Using optimized laser etching technology, transparent areas are created to minimize the adverse effects on electrical properties. These transparent areas can be 25 microns in diameter. The optimization of laser etching technology makes the transparent areas have neutral color rendering (CRI 97) and only 3% haze. The following are the experimental parameters and relevant details of the laser etching technology;

[0031] 1. Laser equipment and configuration

[0032] Laser type: Use nanosecond laser with a frequency of 10kHz and wavelengths of 1064nm and 532nm;

[0033] Scanning system: integrated servo scanner system, enabling fast, precise and flexible laser etching;

[0034] 2. Laser Etching Process

[0035] Environmental conditions: Etching is carried out in a glove box filled with nitrogen to avoid the influence of oxygen, moisture and dust on the sample;

[0036] Etching process: To prevent gas adsorption and debris generated during laser etching from contaminating the sample, a constant laminar nitrogen flow was maintained on the sample surface during laser etching;

[0037] Shape and size of transparent area:

[0038] The small circular transparent area is 25 microns in diameter;

[0039] The diameter of the larger circular transparent area was set to 120 μm to increase the proportion of the highly transparent area;

[0040] A second laser etching is performed in the central part of the transparent area to remove the ITO layer and improve transparency;

[0041] 3. Laser etching parameter optimization

[0042] The shape and distribution density of the transparent area are optimized to reduce the performance loss when the transparency is higher than 30%. By gradually adjusting the density of the transparent area, the transmittance gradient of the laser etching is achieved and ensures that the photoelectric conversion efficiency does not drop significantly when the transparency increases;

[0043] The preparation method of the NiOx layer 2 comprises:

[0044] First, the glass substrate 1 is cleaned in ultrasonic waves with a detergent, deionized water, acetone, and IPA in sequence.

[0045] After drying, treat with UV ozone at 100 degrees Celsius for 10 minutes;

[0046] The NiOx ink was spin-coated on the glass substrate 1 at 3000 rpm for 45 seconds, and then dried on a hot plate at 100 degrees Celsius for 10 minutes to prepare a NiOx layer 2;

[0047] The preparation method of NiOx ink includes:

[0048] 3.635 g of nickel nitrate was dissolved in 2.5 ml of water, and about 2.5 ml of 10 M sodium hydroxide solution was slowly added to the solution to generate a light green Ni(OH)2 precipitate. The precipitate was collected by centrifugation and washed three times with deionized water. The precipitate was transferred to an 80°C oven for drying until the color changed to dark green. The solid was then transferred to a 270°C oven and calcined for 2 hours to obtain NiOx nanoparticles. Finally, the NiOx nanoparticles were dispersed in deionized water at a concentration of 2.6 wt%, and ultrasonically treated for 2 hours and then filtered. Preparation of silver nanowire (AgNW) dispersion The received AgNW dispersion was purified by centrifugation at 2000 rpm for 30 minutes. The precipitate was collected and resuspended in anhydrous isopropanol. The AgNW dispersion was ultrasonically treated for no more than 30 seconds before use.

[0049] The preparation method of the perovskite layer 3 comprises:

[0050] In a glove box, the perovskite precursor solution was spin-coated on the NiOx layer using an anti-solvent technique at speeds of 2000 rpm and 6000 rpm for 10 s and 30 s, respectively. About 10 s into the second stage of spin coating, 100 μl of chlorobenzene was added. Immediately after spin coating, the substrate was transferred to a 100 °C hot plate and kept warm for 50 min.

[0051] The preparation method of the PCBM layer comprises:

[0052] First, a PCBM solution was prepared by dissolving PCBM in DCB at a concentration of 23 mg / ml, and then filtering to form a PCBM solution. The PCBM solution was then spin-coated at 1300 rpm for 40 seconds to form an ETL layer, followed by annealing at 100 degrees Celsius for 5 minutes and cooling for later use.

[0053] The preparation method of the AgNW electrode layer comprises:

[0054] On the PCBM layer 4, the AgNW dispersion was spin-coated at a speed of 900 rpm for 30 seconds, and then dried at 90 degrees Celsius for 30 seconds. A polyimide tape was used as a mask to define the pattern area of ​​the AgNW electrode. The active battery area was typically 0.09 cm 2 , the electrode thickness is increased by repeating the spin coating process;

[0055] The preparation method of the C60 electrode layer 6 comprises:

[0056] First, prepare a C60 solution, dissolve 10 mg / ml of C60 in DCB, heat to 60° C. to dissolve, and then spin-coat the 10 mg / ml C60 solution on the AgNW electrode layer 5 at a spin-coating speed of 1300 rpm for 45 seconds;

[0057] The composite electrode layer formed by the C60 electrode layer 6 and the AgNW electrode layer 5 can improve efficiency and stability and improve interface contact. By adjusting the thickness of the AgNW electrode layer 5, the photoelectric conversion efficiency of the device prepared by the composite electrode layer reached 11.02%. Compared with the battery device without the AgNW electrode layer 5, the PCE of the device with the composite electrode layer increased by 13% to 9.17%.

[0058] After testing, it was found that the efficiency of the device with the composite electrode layer hardly decreased after being stored in a nitrogen glove box for 52 days, showing remarkable stability. The C60 motor layer provided protection for the AgNW and perovskite layer 3, preventing harmful moisture intrusion and corrosion of the silver nanowires.

[0059] The C60 filler achieves a high contact area and favorable energy level gradient alignment on the AgNW network, significantly improving electron transport and interface resistance. Compared with the pure AgNW electrode, the composite electrode formed by the AgNW electrode layer 5 and the C60 electrode layer 6 shows a lower PL intensity in the photoluminescence (PL) test, indicating that it has a superior electron extraction ability.

[0060] In addition, the AgNW electrode layer 5 thin film has high light transmittance and low sheet resistance, and is suitable for manufacturing semi-transparent solar cells; the AgNW electrode layer 5 formed by multi-layer AgNW thin films shows higher efficiency and lower sheet resistance, and the best PCE reaches 11.02%;

[0061] First, with respect to the prior art, the technical solution of this application has the following advantages:

[0062] 1. Balance between electrical and optical properties:

[0063] The prepared perovskite solar cells have a PCE of up to 9.0% at 44% AVT, while maintaining neutral color presentation and low haze of industrial glass quality. AVT is the average visible light transmittance and PCE is the power conversion efficiency.

[0064] 2. Scalability:

[0065] Demonstrated scalability from single solar cells to submodules, achieving 9.0% PCE at 32% AVT with an aperture area of ​​4 cm2;

[0066] The scalability of the technology ensures that these transparent perovskite photovoltaic technologies can be applied in real buildings;

[0067] 3. Prospects of building integrated photovoltaics:

[0068] By introducing the transmission gradient design, the diversity of architectural aesthetics and functions is improved. This design not only meets the needs of photovoltaic energy collection, but also increases the aesthetics and personalization possibilities of the building facade.

[0069] The technical solution of the present invention is described above in conjunction with specific implementation methods, but it should be noted that the above descriptions are only for explaining the solution of the present invention and cannot be interpreted in any way as a specific limitation on the scope of protection of the invention. Based on the explanation here, those skilled in the art can think of other specific implementation methods or equivalent replacements of the present invention without creative work, and they will all fall within the scope of protection of the present invention.

Claims

1. A semi-transparent laminated perovskite cell, characterized in that: The perovskite cell includes a glass substrate, a NiOx layer, a perovskite layer, a PCBM layer, an AgNW electrode layer, and a C60 electrode layer. The glass substrate, the NiOx layer, the perovskite layer, the PCBM layer, the AgNW electrode layer, and the C60 electrode layer are arranged in sequence from bottom to top, and the perovskite layer is micro-patterned by laser etching technology.

2. A semi-transparent laminated perovskite cell according to claim 1, characterized in that: The preparation method of the NiOx layer comprises: The glass substrate was first cleaned in ultrasonic waves with detergent, deionized water, acetone, and IPA in sequence, and then dried and treated with UV ozone at 100 degrees Celsius for 10 minutes; Spin coating the NiOx ink on the glass substrate at 3000 rpm for 45 seconds, followed by drying on a hot plate at 100 degrees Celsius for 10 minutes to prepare a NiOx layer; The preparation method of the NiOx ink comprises: 3.635 g of nickel nitrate was dissolved in 2.5 ml of water, and about 2.5 ml of 10 M sodium hydroxide solution was slowly added to the solution to generate a light green Ni(OH)2 precipitate. The precipitate was collected by centrifugation and washed three times with deionized water. The precipitate was transferred to an 80°C oven and dried until the color turned dark green. The solid was then transferred to a 270°C oven and calcined for 2 hours to obtain NiOx nanoparticles. Finally, the NiOx nanoparticles were dispersed in deionized water at a concentration of 2.6 wt%, and ultrasonically treated for 2 hours and then filtered.

3. A semi-transparent laminated perovskite cell according to claim 1, characterized in that: The preparation method of the perovskite layer comprises: In a glove box, the perovskite precursor solution was spin-coated on the NiOx layer using an anti-solvent technique at speeds of 2000 rpm and 6000 rpm for 10 seconds and 30 seconds, respectively. When the second stage of spin coating was about 10 seconds, 100 μl of chlorobenzene was added. After the spin coating was completed, the substrate was immediately transferred to a 100°C hot plate and kept warm for 50 minutes.

4. A semi-transparent laminated perovskite cell according to claim 1, characterized in that: The preparation method of the PCBM layer comprises: First, a PCBM solution was prepared by dissolving PCBM in DCB at a concentration of 23 mg / ml, and then filtering to form a PCBM solution. The PCBM solution was then spin-coated at 1300 rpm for 40 seconds to form an ETL layer, followed by annealing at 100 degrees Celsius for 5 minutes and cooling for later use.

5. The semi-transparent laminated perovskite cell according to claim 1, characterized in that: The preparation method of the AgNW electrode layer comprises: On the PCBM layer, AgNW dispersion was spin-coated at a speed of 900 rpm for 30 seconds and then dried at 90 degrees Celsius for 30 seconds. Polyimide tape was used as a mask to define the pattern area of ​​the AgNW electrode. The active cell area was typically 0.09 cm 2 , the electrode thickness was increased by repeating the spin coating process.

6. The semi-transparent laminated perovskite cell according to claim 1, characterized in that: The preparation method of the C60 electrode layer comprises: First, prepare a C60 solution, dissolve 10 mg / ml of C60 in DCB, heat to 60° C. to dissolve, and then spin-coat the 10 mg / ml C60 solution on the AgNW electrode layer at a spin-coating speed of 1300 rpm for 45 seconds.